(untitled) (Research, Society and Development, 2022)
Belonging to the Arecaceae Family, the species: Butia lallemantii and Syagrus romanzoffiana, known respectively as butiá-anão and jerivá, are of high economic and cultural value. They occur in the State of Rio Grande do Sul and both species cohabit the locality of Cerro do Tigre- Alegrete/RS, which allowed the crossing between the species, Originating the natural interspecific hybrid x Butyagrus alegretensis. The objective of this study was to analyze and compare morfometries between the individuals of the three species, since Works using morphological characters are important in the species identification process. Data were collected from eight variables: from five individuals of each species, totaling fifteen matrices. To obtain the statistical data: mean, analysis of variance, correlation matrix and comparative testo f means, the software Genes was used. Regarding the averages, the individuals representing S. romanzoffiana were superior, followed by B. alegretensis and B. lallemantii respectively, in the correlation analysis we identified the petiole length is a good character in the differentiation of the species, besides that we could observe that statistically the species hybrid more closely resembles the parental B. lallemantii. We hope that the use of these data can help in the identification of species and serve as a basis for future Works aimed at bater elucidation of these species.